Influence of Zr-1 wt.% Nb alloy structure state on its deformation and thermal behavior under quasi-static tension; Materials Letters; Vol. 285 - Legostaeva E. V. Elena Viktorovna; Sharkeev Yu. P. Yury Petrovich; Eroshenko A. Yu. Anna Yurjevna; Belyanskaya O. A. Olga; Vavilov V. P. Vladimir Platonovich; Skripnyak V. A. Vladimir Albertovich; Ustinov A. M. Artem Mikhaylovich; Klopotov A. A. Anatoly Anatoljevich; Chulkov A. O. Arseniy Olegovich; Kozulin A. A. Aleksandr Anatoljevich; Uvarkin P. V. Pavel Viktorovich; Skripnyak V. V. Vladimir Vladimirovich (2021, 2021)
Title screen